KEMAMPUAN BERPIKIR GEOMETRI BERDASARKAN TEORI VAN HIELE DENGAN GAYA KOGNITIF FIELD INDEPENDENT - Oktarini, Dwi; Ariani, Nyayu Masyita (Universitas Muhammadiyah Bengkulu, 2016)
This research aims to describe the geometric thingking ability of students in the quadrilateral and triangular material based on the Van Hiele theory to grade VII B SMPN 9 Kota Bengkulu who have field independent (FI) cognitive style. The type of this research is qualitative descriptive. The Data were obtained from Van Hiele geometry test results and interviews. Ones were analyzed by using qualitative data analysis techniques. The results showed that FI’s students able to analyze problems of geometry well and in responding to such questions based on the requirements from the inside. So the ability of the highest FI’s students can be achieved to ability level from level 2 to the level 3 (Pre deduction).Keywords : Geometry Thinking, Van Hiele Theory, Field Independent (FI)